Tourism non-places: Bending airports and wildscapes. (January 2020) - Varley, Peter; Schilar, Hannelene; Rickly, Jillian M.
Abstract: This paper takes Augé's non-place idea as point of departure to develop a deeper phenomenological understanding of two types of tourism settings: wild spaces and airports. While place and non-place are useful as comparative, polarized concepts addressing materialities and subjective experiences, asking what these particular spaces are like sheds light on both their bendability and boundedness, revealing the potential of intentionality in liberating place experiences. While intentionality has not yet received much attention in industry or scholarly discussions of tourism, it is absolutely crucial to the experience of tourism, as our findings elaborate on the ways travellers accede to and consume (non-) places, as well as negotiate, conquer and extemporise them. Highlights: Reconsiders Augé's non-place idea for tourism Compares wild spaces and airports to assess the limits of non-places Infuses the concept of intentionality into (non-) place experiences Evidences practice that travellers accede to, consume and conquer non-places.